2023
DOI: 10.3390/ijms24020986
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Cellulose-Based Blends and Composites: Versatile Biomaterials for Tissue Engineering Applications

Abstract: Cellulose of bacterial origin, known as bacterial cellulose (BC), is one of the most versatile biomaterials that has a huge potential in tissue engineering due to its favourable mechanical properties, high hydrophilicity, crystallinity, and purity. Additional properties such as porous nano-fibrillar 3D structure and a high degree of polymerisation of BC mimic the properties of the native extracellular matrix (ECM), making it an excellent material for the fabrication of composite scaffolds suitable for cell gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 200 publications
(261 reference statements)
0
23
0
1
Order By: Relevance
“…On their website, 216 it seems to be only available in Brazil. 19,25,[217][218][219] KKF polymers is a company who was previously named Jenpolymer as a start-up. The company was founded from a group of more than 60 Ph.D. from the University of Jena, Germany.…”
Section: Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…On their website, 216 it seems to be only available in Brazil. 19,25,[217][218][219] KKF polymers is a company who was previously named Jenpolymer as a start-up. The company was founded from a group of more than 60 Ph.D. from the University of Jena, Germany.…”
Section: Medicalmentioning
confidence: 99%
“…Another company that is well present in review articles for BC used in the medical industry is a company named Xylos Corporation located in Langhorne, United States. 19,25,217,218,226 Their wound dressing XCell has been clinically studied regarding its ability to autolytically remove non-viable tissue and create a healthy wound bed. 227 In a review by Ludwicka et al, the authors mention XCell was purchased from Xylos Corporation by Lohmann & Rauscher and re-commercialized under the name Suprasorb.…”
Section: Medicalmentioning
confidence: 99%
“…When production is performed statically, the membrane has a flat appearance and takes on the shape of the vessel in which fermentation took place. With dynamic production, the final product looks like pearls/pellets or dispersed fibres [ 35 , 36 , 37 ].…”
Section: Bacterial Cellulosementioning
confidence: 99%
“…When degraded before arriving at the action sites, only trace amounts of this kind of protein are in effect. Recently, apart from some molecules [ 8 , 9 ], it was reported that polysaccharides have neurotrophic factor-like effects, and a variety of natural polysaccharides, including MAPs from Opuntia Milpa Alta [ 10 ], polysaccharides from Rosa roxburghii [ 11 ], GLPS from Ganoderma lucidum and fucoid from brown seaweeds, were reported to exhibit neurotrophic or neuroprotective activity [ 12 ]. The neuroprotective effect of polysaccharides has received increasing attention.…”
Section: Introductionmentioning
confidence: 99%